Effectiveness of Sustainable Design and Costing Practices in Construction: A Cross-Sectional Survey of Professionals’ Roles Towards Resource Conservation - Amadi Alolote Ibim1; Kelechukwu Dimkpa (International Journal of Industrial and Product Design Engineering, 2025)
Climate change and the continuous depletion of natural resources have significant implications for the built environment. Sustainable construction has thus become topical, with measures being widely discussed on how to integrate it into proposed product design development, necessary to ensure resource conservation. This study evaluates the role of built environment design and costing professionals in sustainable construction, exploring their contributions towards resource conservation, and their effectiveness in implementing sustainable practices within the construction industry. The study carried out a cross-sectional survey focused on Rivers State due to the current vibrant construction and development activities. A selective sampling technique was adopted in selecting experienced professionals from the database/separate list of professional organizations in the study area that met the study criteria. The findings show that role of architectural designs and specifications in enhancing sustainable construction is widely acknowledged within the built environment. By preserving the ideal balance above cost and sustainability, the quantity surveyor, working in tandem with the architect, is critical for the development of energy-efficient and ecologically friendly buildings. The findings indicate that architects and quantity surveyors play key roles in resource conservation such as by the implementation of life cycle costing methodologies, with due consideration of resource consumption throughout the entire lifespan of proposed construction. Furthermore, they play vital roles in sustainability assessment, performance evaluation, and value integration to a great extent. The results of the study thus indicate that built environment professionals, particularly architects and quantity surveyors play a significantly role in resource conservation as a fundamental measure necessary for attaining sustainability in construction.
Keywords: Built environment; professionals; resource conservation; sustainable construction; traditional roles